OP64 Impact of poverty trajectories on children's health and maternal mental health: evidence from the UK millennium cohort study. (September 2018) - Wickham, S; Lai, ETC; Barr, B; Taylor-Robinson, DC
Abstract : Background: The number of children living in poverty in the United Kingdom (UK) is rising. Child poverty has been shown to cause poor mental and physical health outcomes that last into adulthood. Poverty also puts families in distress. The aim of the study was to understand the prevalence of different poverty trajectories for UK children, and their associations with multiple child health and maternal mental health outcomes. Methods: We analysed data on 11 565 children who participated in sweeps of the UK Millennium Cohort Study from ages 9 months to 14 years. Outcomes were: (i) mental health at age 14, measured by the Strengths and Difficulties Questionnaire (SDQ); (ii) physical health at age 14, measured by overweight/obese and any longstanding illness; and (iii) maternal mental health, measured by Kessler 6 scale. The main exposure of interest was relative poverty (less than 60% of median of equivalised household income). Poverty trajectories measured at 9 months, 3, 5, 7, 11 and 14 years were characterised using latent class analysis. Odds ratios (ORs) and 95% confidence intervals (CIs) were estimated using multivariable logistic regression models, adjusted for child sex, maternal education and maternal ethnicity. Results: Four poverty trajectories were identified: class 1 (61.2% of children) (stable never-poor, reference group), class 2 (14.2%) (poverty in early childhood), class 3 (5.2%) (poverty in late childhood) and class 4 (19.4%) (persistent poverty). Any exposure to poverty was associated with increased risk of longstanding illness, and worse mental health outcomes for both mothers and children, with the largest effects for persistent poverty. Compared with children who were never poor, those from persistently poor households were at a higher risk of having mental health problems [SDQ score ≥17 (aOR: 2.76; 95% CI 2.29 to 3.34)], physical health problems [being overweight/obese (aOR: 1.23; 95% CI 1.07 to 1.41); longstanding illness (aOR: 1.82, 95% CI 1.55 to 2.15)] and mothers under psychological distress [Kessler 6 scale score ≥6 (aOR: 2.60; 95% CI 2.26 to 3.00)]. Conclusion: Persistent poverty affects one in five UK children and is associated with negative impacts on child and maternal health, particularly mental health. Any exposures to poverty mainly in early or late childhood were also associated with worse outcomes. One of the limitations of this study is that household income was self-reported. Policies that reduce child poverty and its consequences are likely to improve health across the life course.